Porphyromonas gingivalis Promotes Colorectal Carcinoma by Activating the Hematopoietic NLRP3 Inflammasome - Wang, Xi; Jia, Yiqun; Wen, Liling; Mu, Wenxin; Wu, Xianrui; Liu, Tao; Liu, Xiangqi; Fang, Juan; Luan, Yizhao; Chen, Ping; Gao, Jinlong; Nguyen, Ky-Anh; et al. (Cancer research (Chicago, Ill.), 2021)
( ) is a keystone periodontal pathogen associated with various digestive cancers. However, whether can promote colorectal cancer and the underlying mechanism associated with such promotion remains unclear. In this study, we found that was enriched in human feces and tissue samples from patients with colorectal cancer compared with those from patients with colorectal adenoma or healthy subjects. Cohort studies demonstrated that infection was associated with poor prognosis in colorectal cancer. increased tumor counts and tumor volume in the mouse model and increased tumor growth in orthotopic rectal and subcutaneous carcinoma models. Furthermore, orthotopic tumors from mice exposed to exhibited tumor-infiltrating myeloid cell recruitment and a proinflammatory signature. promoted colorectal cancer via NLRP3 inflammasome activation and . NLRP3 chimeric mice harboring orthotopic tumors showed that the effect of NLRP3 on pathogenesis was mediated by hematopoietic sources. Collectively, these data suggest that contributes to colorectal cancer neoplasia progression by activating the hematopoietic NLRP3 inflammasome. SIGNIFICANCE: This study demonstrates that the periodontal pathogen can promote colorectal tumorigenesis by recruiting myeloid cells and creating a proinflammatory tumor microenvironment. GRAPHICAL ABSTRACT: http://cancerres.aacrjournals.org/content/canres/81/10/2745/F1.large.jpg.